Role Of Agricultural Sector In Facing Economic Disparity In The Special Province Of Yogyakarta - Arif Wahyu Widada; Jangkung Handoyo Mulyo; Muh Amat Nasir (Universitas Muhammadiyah Jember, 2020)
GRDP (Gross Regional Domestic Product) growth is one indicator of economic growth in a region. This indicator should not only rise but must also be evenly distributed in the surrounding area. This study aims to (1) further investigate the contribution of the agricultural sector in the GRDP in DIY, and (2) determine the role of the agricultural sector in dealing with economic disparity in DIY. This study used secondary data covering several variables from 2010-2018. The analytical tool used was table description analysis, calculated Williamson index, paired t-test, and simple OLS regression. The results of the study reveal that the agricultural sector has a declining contribution to the GRDP in DIY. There is an increase in regional income gaps or economic growth between districts/cities in DIY. The agricultural sector is significantly proven to have an impact on the decline in the Williamson Index, which means that the higher the contribution of the agricultural sector to the district/city GRDP, the economic growth between regions in DIY is more evenly distributed. In other cases, the agricultural sector can reduce economic disparities between districts/cities in DIY.